Controle social e participação popular no Sistema Único De Saúde (SUS) - Andrade, Amanda Figueiredo de (2022)
The right to health is recognized as a human, fundamental and social right, appearing in the Constitution as a right for all and a duty of the State. It was designed to be fulfilled through the Unified Health System, one of the achievements of Brazilian redemocratization, which consists in a regionalized and hierarchical network at the national level. The legislation governing the Unified Health System brought popular participation as a principle to be observed, in order to ensure that the population participates in the process of formulating and controlling public health policies. However, although the norm that advocates popular participation exists at the normative level, it is not perceived in social reality. Therefore, there is a contrast between the normative plan, since the norm exists and is in force, and the reality experienced by the Brazilian population, since its effects either do not appear or do not correspond to social demands in social reality. Therefore, the research problem revolves around the verification of the causes of the deficiency of popular participation in the Unified Health System, based on indicators extracted from the work “La constitución de la democracia deliberativa”, by Carlos Santiago Nino (1997), in contrast to to the results of surveys carried out in different places to assess popular participation in the SUS, based on the presupposition of the deficiency of this participation. In view of this, the hypothesis raised is that the existing and propagated means of popular participation within the scope of the Unified Health System have characteristics of an opaque right, according to the concept of Carlos María Cárcova (1998) in the work “A opacidade do direito”, due to (a) the lack of knowledge about the means of participation and (b) a fictitious popular participation, since the quality of representation leaves significant minorities, who are the most in need of the public health system, apart from the discussion. The main objective of this research is to verify the opacity of popular participation in the Unified Health System. Initially, democracy and popular participation in the Unified Health System were discussed, discussing issues of the relationship between constitutionalism and democracy, and finally discussing deliberative democracy in the work “La constitución de la democracia deliberativa”, by Carlos Santiago Nino (1997), scoring indicators to assess social participation and social control in the Unified Health System. Then, the right to health was discussed, as a social right, passing through the theme of material equality and social control in health and the sanitary norms on social control in health. Finally, the ineffectiveness that exists regarding social control in the Unified Health System was analyzed, demonstrating it through data analysis about popular participation in the means provided for in the Health Councils and in other means of participation, based on selected studies carried out in Brazil, based on indicators of political apathy, impoverishment of the debate and the imperfection of intermediation, according to the work of Nino (1997). For the first hypothesis, it was concluded that the central problems identified in the research are not mostly the lack of knowledge about the means of participation, but the political apathy, which generates the impoverishment of the debate and the quality of the solutions found, according to concepts of Carlos Santiago Nino (1997) in the work “La constitución de la democracia deliberativa”. The second hypothesis was identified in the problem of the quality of representativeness perceived in the analyzed studies. It was concluded that such problems are fueled by the factor of Brazilian inequality, generating a sub-integration of a certain portion of the population, and it is essential that this problem is faced so that social control and popular participation in the Unified Health System are achieved.